COVID-19 the intruder: A philosophical journey with Jean-Luc Nancy into pandemic strangeness and tourism. (July 2022) - Munar, Ana María; Doering, Adam
Abstract: Since the arrival of COVID-19, tourism scholarship has focused its attention on rethinking and restarting the tourism sector. In this urgent search for a 'new normal', the embodied experience of hosting such an unwelcomed virus, the philosophical questions this raises, and the tourism futures already in the making, have not been fully explored. The article introduces Nancy's (2000/2002) philosophy, L'intrus [The Intruder], where he reflects on having a heart transplant operation to give body to the experiences of the self as exteriority and of otherness always already within. We take inspiration from Nancy to think and sense the experience of the COVID-19 virus intrusion in tourism. To do this, we weave personal philosophical reflections with ethnographic material to reflect on three themes of intrusion for tourism scholarship to consider: the experience of a body/self as exposed, the experience of a shattered self, and the experience of uncertain futures. Highlights: Introduces Jean-Luc Nancy's philosophy of intrusion for tourism studies. Philosophizes tourism through personal reflection and lived experience. Reveals the body in tourism as multiple and exposed. Challenges managerial approaches to the tourism experience. Dwelling in strangeness questions discourses of tourism recovery and the 'new normal'.